Hungary : Second Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Request for Modification of Performance Criteria; Staff Report; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2009)
This paper discusses key findings of the Second Review under the Stand-By Arrangement for Hungary. All end-March 2009 quantitative performance criteria and the continuous performance criterion on nonaccumulation of external arrears were met, as well as the end-March indicative target on central government debt. The end-March structural performance criteria related to pension reform and government lending to banks were met. The structural performance criterion on amendments to the Financial Stability Act was not fully met but, on the basis of the corrective action taken, IMF staff supports the authorities' request for a waiver.